Study on DNA repeats using finite rate of innovation theory - Bui Vu Long (2010)
Tandem repeats (TRs) consists of repetitions of a pattern of nucleotides and occurs frequently in the human genome. They are commonly used in human gene mapping, linkage studies, and forensic DNA fingerprinting analysis. It has been recently proved that TRs cover more than ten percent of human genome and play an important role in human diseases, regulation and evolution. Hence, identifying TRs fast and accurately within DNA sequence is one of the most hot topic for bioinformatics. Although there exist number of researches on TRs, each of them has its own limitation. Requiring the certain prior information for searching TRs is the common obstacle to these algorithms since in most situations, it is impossible to get these information beforehand. That’s the reason why this project exists. Since 2007, the proposed DNA compression algorithm applying sampling signal with finite rate of innovation (FRI) theory has made the stepping stone in modeling DNA as the FRI signal. It created opportunities for performing DNA analysis in sampling domain instead of alphabet domain. Because of potential DNA performance in sampling domain and TRs importance in human gene, the project will study the behavior of TRs in DNA sequence. From that, the student hoped to proposed a better algorithm which overcomes the common problem facing by existing algorithms. Since this is the first time that one of the DNA sequence analysis will be performed on sampling domain using FRI theory, it will create promising areas and research topics for other DNA analysis if successful.